Smoke check a study on the effects of NCR male high school students exposure to and recall of anti-smoking advertisements to their perceptions of and attitudes toward smoking - Aguillon, Joyce Mendoza (2012)
"The study aims to determine the effects of the extent of exposure to anti-smoking advertisements and the recall of National Capital Region (NCR) male high school students to their perceptions of and attitudes toward smoking. Male students were chosen because the 2007 Global Youth Tobacco Survey estimates that there are 17% or 4 million Filipino youths with ages 13-15 years who are smoking. Of these early starters, 2.8 million are boys and 1.2 million are girls, thus majority are male in high school level. The Health Belief Model (HBM), Mere Exposure Theory, and Availability Heuristics Principle were used for the theoretical framework of the study. A survey was conducted randomly among 400 NCR male high school students. The researchers also conducted two Focus Group Discussions divided to smokers and nonsmokers. Results found out that three in ten NCR male high school students had tried smoking at ages 12 to 14 years. There was a high general perceived susceptibility and severity of having smoking-related diseases among the NCR male high school students. The general attitude of the students toward smoking was either positive or negative (neutral). The study also found out that there was a weak correlation between the NCR male high school students' exposure to and recall of anti-smoking advertisements and their perceptions of and attitudes towards smoking."